Measuring climate policy stringency: A shadow price approach using energy prices - Erik Hille; Wilhelm Althammer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
To assess the effect of environmental policy on production structures, trade structures or foreign direct investment, a measure for the stringency of policy is necessary. Measures typically used in empirical studies share several disadvantages: They are not available on a sectoral basis to reflect concerns of industry competitiveness; they are not available for a wide range of countries to allow for international comparisons; or they are not broad enough to reflect the multidimensionality of environmental policy. This paper develops a thorough, internationally comparable, sector-specific measure of multidimensional climate policy stringency where a shadow price approach serves as a basis. The approach is applied to climate policy by determining sector-specific emission relevant energy costs on the basis of the sectors usage of emission relevant energy carriers and the carriers respective prices. The resulting shadow price estimates are heterogeneous and can be applied in future research to test for carbon leakage and pollution havens.
Keywords: D22; Q48; Q54; 330